Correlation Between Coronary Artery Ectasia and Past Stressful Life Events and Psychological Hardiness: A Cross-Sectional Analysis - Korkmaz, Hasan; Yaman, Irfan; Sarioglu, Guney; Tabara, Muhammed Fatih; Molu, Esengul; Korkmaz, Sevda (Mdpi, 2026)
Background and Objectives: Coronary artery ectasia (CAE) is defined as a localized or diffuse dilatation of the coronary arteries and is often associated with atherosclerosis, congenital factors, or inflammatory conditions. Given emerging evidence that psychological factors may influence cardiovascular health, this study investigated whether psychological hardiness and past traumatic experiences are associated with CAE. Materials and Methods: This study employed a retrospective, cross-sectional, observational design involving 80 participants. All participants were administered a socio-demographic data form, the Beck Depression Inventory (BDI), the Beck Anxiety Inventory (BAI), the Personal Views Scale III-R (PVS III-R), and the Stressful Life Events Screening Form (SLESF). Results: The PVS III-R scale score for patients with CAE was significantly higher than that of the control group. The SLESF scores were markedly lower in the CAE group when compared to the control group, demonstrating that the control group experienced substantially more intense traumatic events when compared to CAE patients. Binary logistic regression was applied to determine variables associated with CAE, and the results were statistically significant. Notably, higher self-reported PVS III-R scores were independently associated with the presence of CAE. Conclusions: This study may provide a preliminary psychosomatic perspective on the pathophysiology of CAE, emphasizing the complexities of mind-body interactions. It suggests that high psychological hardiness may be associated with unexpected biological outcomes and warrants further investigation.
Keywords: psychological hardiness; coronary artery ectasia; stressful life events